Physiological status of high and low metabolism Hevea clones in the difference stage of tapping panel dryness - RADITE TISTAMA; PUTRI ARISMA SIREGAR MAWADDAH; LUBIS ADE-FIPRIANI; JUNAIDI JUNAIDI (Society for Indonesian Biodiversity, 2019)
Abstract. Tristama R, Mawaddah PAS, Ade-Fipriani L, Junaidi. 2019. Physiological status of high and low metabolism Hevea clones in the difference stage of tapping panel dryness. Biodiversitas 20: 367-373. Tapping panel dryness (TPD) caused productivity of rubber trees drop sharply. However, the increase of TPD stage has not been completely elucidated, especially in physiological aspects. TPD incident was higher occurred in high metabolism than low metabolism clones. The incident has been classified based on visual observation. This research aimed to explore the physiological characters to identifying the physiological changes of each TPD stage in the two metabolism types of rubber clones, IRR 42 (low metabolism) and IRR 118 (high metabolism). The physiological parameters such as thiol, Pi content and peroxidase activity were specifically in each clone and the tissue types (bark or laticifer). The physiological pattern of IRR 42 was a difference with that of IRR 118 for the increase of the TPD stages. Phosphate inorganic content in the latex and bark were a decline in the TPD affected trees, whereas the sucrose content was relatively constant. The pattern of changes of thiol content in IRR 42 was reverse with IRR 118, both in the latex or bark tissue. Peroxidases activity in the latex and bark negatively correlated with the TPD stage. The decline of Pi and peroxidase activity can be used to identify the TPD incident in rubber trees.